Surgical management of compensatory sweating: A systematic review - Loizzi, Domenico; Mongiello, Diletta; Bevilacqua, Maria Teresa; Raveglia, Federico; Fiorelli, Alfonso; Congedo, Maria Teresa; Ardò, Nicoletta Pia; Sollitto, Francesco (Frontiers in Surgery, 2023)
Endoscopic thoracic sympathectomy (ETS) surgery is a highly effective treatment of primary hyperhidrosis (PH) for the palms, face, axillae. Compensatory sweating (CS) is the most common and feared side effect of thoracic sympathectomy. CS is a phenomenon characterized by increased sweating in sites distal to the level of sympathectomy. Compensatory sweating is the main problem for which many patients give up surgery, losing the chance to solve their problem and accepting a poor quality of life.There are still no treatments that offer reliable solutions for compensatory sweating. The treatments proposed in the literature are scarce, with low case histories, and with uncertain results. Factors associated with CS are extension of manipulation of the sympathetic chain, level of sympathetic denervation, and body mass index. Therapeutic options include non surgical treatment and surgical treatment. Non surgical treatments include topical agents, botulinum toxin, systemic anticholinergics, iontophoresis. Surgical treatments include clip removal, extended sympathectomy and sympathetic chain reconstruction, although the efficacy is not well-established for all the methods. In this review we provide an overview of the treatments and outcomes described in the literature for the management of compensatory CS, with focus on surgical treatment.